Compressive Strength Behavior of Clay Admixed Cement Under the Different Curing Conditions - Phojan, Worawit; Leeanansaksiri, Anuchat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This study investigated the unconfined compressive strength of cemented clay under soaked and unsoaked conditions. The concept of the study was the use of a soil-cement core zone for check dam construction. The check dam needs fast construction and must be immediately soaked in water after the end of construction. Influential factors of this study were cement content, water content, soaked/unsoaked conditions and curing times. The cement contents were 15, 20 and 25 % by weight of dry soil. The moisture contents were 80, 100 and 120 % of optimum moisture content. The study results indicated that unconfined compressive strength increased with an increase in curing time for all mixing ratios. The lower clay- water/cement ratio resulted in an increase in unconfined compressive strength. The results of soaked and unsoaked conditions showed that soil-cement samples in soaked conditions had lower compressive strength than those in unsoaked conditions. However, soil-cement samples in soaked conditions had more yield strength and ductility than soil-cement samples in unsoaked conditions. The effect of the initial soaked condition resulted in the clay-water/cement ratio increase in the unconfined compressive strength of samples in soaked condition lower.